REPLY TO COMMENTS FROM S.G. SKUBLOV, A.V. BEREZIN, AND L.I. SALIMGARAEVA ON THE ARTICLE AUTHORED BY M.V. MINTS AND K.A. DOKUKINA – THE BELOMORIAN ECLOGITE PROVINCE (EASTERN FENNOSCANDIAN SHIELD, RUSSIA): MESO-NEOARCHEAN OR LATE PALEOPROTEROZOIC? - M. V. Mints; K. A. Dokukina (Геодинамика и тектонофизика)
In their research, the authors of the comments have focused on the Late Paleoproterozoic rims of zircons, but ignored many important details of their own data. Their comments are based on a misconception that eclogite zircons have unique geochemical (REE, Th/U) and isotopic (Lu-Hf, δ18O) characteristics that do not depend on rock types and pressure rates (that were high or ultrahigh) during metamorphism. This idea leads to false unambiguous dating of the eclogite facies metamorphism based on single samples of the rocks.